Study on Skin Separation in Majhul Fruits - Lustig, Itzchak; Bernstein, Z.; Gophen, Moshe (Recent Progress in Plant and Soil Research Vol. 3, 2021)
Skin separation in ripe date fruits is not only an unpleasant quality, but it also reduces the market value of the fruit and causes financial loss to the growers. The skin defines the shape of the fruit during pre-ripped stages as a result of the internal turgor pressure. According to our studies, it is induced in part by high diurnal, cyclic stressors of turgor pressure changes prior to the fruit's ripening stage, and it is also influenced by environmental factors. It was also discovered that the mechanical qualities of ripe fruit skin in Majhul dates affect the separation of the soft tissues. The mechanical characteristics (visco-elasticity) of separated and non-separated fruit skin were found to be significantly different in our experiment. It is suggested that procedures for preventing skin separation be used.